PEMASARAN PRODUK SECARA ONLINE PADA UMKM FLOBAMORA COLLECTION YANG BERBASIS WEBSITE - Jofret Umbu Soru Peku Djawang; Alya Elita Sjioen; Theodora Teresa Ina (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2022)
Marketing of Flobamora Collection products is currently still done manually through Toko, Facebook and word of mouth where sales only cover Kupang City, while for customer segment opportunities, Flobamora Collection products are very broad. The purpose of the activity is to provide product marketing training and use of website media to expand sales and promotion of Flobamora Collection products so that they are better known by the wider community. The method used in community service activities is to conduct training and practice in implementing online product marketing at the website-based Flobamora Collection. The results achieved in this activity are increasing partner knowledge about website-based online product marketing models and increasing partner understanding about the use of online stores as a medium to sell and promote Flobamora Collection products. Creating a website-based online store as a medium to sell and promote products online. By utilizing webiste-based online marketing media, it can enable the wider community not only in the Kupang City area but also nationally and even abroad to access information on the products offered by Flobamora Collection, thereby increasing the number of customers and sales turnover of Flobamora Collection.